Coexistence mechanisms of sympatric ungulates: Behavioral and physiological adaptations of blue sheep (Pseudois nayaur) and red deer (Cervus elaphus alxaicus) in Helan Mountains, China - Li, Zongzhi; Wang, Jifei; Khattak, Romaan Hayat; Han, Xingzhi; Liu, Peng; Liu, Zhensheng; Teng, Liwei (Frontiers in Ecology and Evolution, 2022)
Studying the coexistence mechanisms of sympatric wildlife helps to shed light on why the earth has so many different species. When ungulates share ranges, food and habitat requirements may partially or fully overlap. Therefore, the aim of this study was to determine how sympatric ungulates share limited resources. Carcasses of 27 adult blue sheep (Pseudois nayaur) and three adult red deer (Cervus elaphus alxaicus) were collected in the Helan Mountains, China. Nutritive indices of plant species foraged and morphometric measurements of the digestive system of the two sympatric ungulates were determined. In addition, 120 passive, infrared motion-triggered cameras recorded spatial and temporal overlap between the two species. Camera trapping revealed relatively limited spatial overlap and significantly different activity rhythms between blue sheep and red deer. Differences were also observed in stomach weight, surface enlargement factor of the rumen, and intestine length between the two species. However, the combined relative weight of stomach and intestine was not different between species. The low spatiotemporal overlap decreased opportunities for encounters between sympatric blue sheep and red deer, and significant differences in digestive systems allowed the two species to consume different plant species or different parts of the same species. Thus, the two sympatric ungulates coexist harmoniously in the Helan Mountains because of long-term evolutionary behavioral and physiological adaptations that eliminate negative effects on survival of the other species.